(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article analyzes the most modern changes in the rules of the popular and mass sports game - futsal. Futsal is an effective means of physical education for all age groups and contributes to the physical development and strengthening of the health of children, young people, middle-aged and older people. Futsal takes a significant place in the system of physical education of schoolchildren and student youth, has a great health, educational and educational value. Research materials can be used in the educational processes of educational institutions when teaching the discipline of sports games for the professional training of bachelors of physical education and sports, for the training offuture specialists in physical culture and health activities, at training courses for futsal coaches, for seminars on the training of referees and observers of futsal refereeing of all levels. Futsal should be attractive and enjoyable for players, match officials, coaches, as well as spectators and fans, The rules should help make the game more attractive and enjoyable for people regardless of their age, race, religion, culture, ethnicity, gender, sexual orientation, physical limitations, etc., and make them want to participate and enjoy their participation in sport game futsal. At the same time, in order to fulfill these needs, the International Federation of Football Associations has to make changes to the Laws of the Game in accordance with today’s requirements. Many changes were based on suggestions from ordinary people, teams and national futsal associations. Over the past ten years, there have been four official reissues of the Rules of the Game, the most recent of which came into force in November 2023. The analysis of changes that affect the technical, tactical and safety components of the sports game - futsal - is relevant.